Korelasi Emisi Karbon dengan Pasar Modal dan Pertumbuhan Ekonomi di Indonesia - Hary S. Sundoro; Grace Putlia (Universitas Batanghari Jambi, 2026)
This study aims to determine the relationship between carbon emissions and capital market performance and economic conditions in Indonesia during the period 2022.12-2025.7. The research method used is the Vector Error Correction Model (VECM) with the help of Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) analysis. The results of this study indicate that carbon emissions are negatively related to the capital market index and GDP, especially in the long term. Carbon emissions are more influenced by the capital market index (LCL-45) than by GDP. However, carbon emissions are most influenced by the carbon emission variable itself. This means that environmentally friendly business activities such as the use of renewable energy are needed in addition to continuing business operations, but carbon emissions can be reduced. In addition, beyond business and economic activities, environmental conservation activities are also needed to reduce carbon emissions.